Clinical researchThe prevalence of obesity of children (aged 13-15) and the significance of selected obesity risk factors - Zawodniak-Szałapska, Małgorzata; Stawerska, Renata; Lewiński, Andrzej (Archives of Medical Science, 2007)
Introduction: Childhood obesity has become a global epidemic. The aim of the study was to assess obesity prevalence in a group of children aged 13-15 in the urban and rural environment of the Lodz region and to establish the influence of selected obesity risk factors. Material and methods: The study involved 1012 children, aged 13-15, and was performed in two secondary schools located in the city and two in the country. In each case, body height and weight were measured and BMI was calculated; also the perinatal data, the duration of breastfeeding, and the prevalence of obesity and type 2 diabetes within children’s families were recorded. Results: The prevalence of obesity in the studied population was 18.1%, being higher in the urban population than in the rural one. The prevalence of obesity of the relatives of obese children was higher (43.7%) than that of children with normal body weight (26.7%). No correlation was found between current BMI and birth weight; however, hypotrophy was more frequently observed among obese children from the rural environment. No significant differences were found between the duration of breastfeeding of obese and slim children. Conclusions: The prevalence of obesity in the age group 13-15 is 18.1% and it is higher in the urban population than in the rural one. Obesity history in the child’s family is an important risk factor of childhood obesity. No correlations between current BMI and birth weight or the duration of breastfeeding in this age group were observed.